Potensi Ekstrak Kulit Daun Lidah Buaya sebagai Bahan Antibakteri pada Active Film Berbasis Pektin - Herza Govina Sobarsa; Nugraha Edhi Suyatma; Harsi Dewantari Kusumaningrum (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2023)
Edible film is a thin layer made of materials that can be consumed, protect from moisture and gas, and extend the shelf life of food products. The criteria for the materials for edible films are able to withstand gas and water permeation, colorless, do not cause changes in the characteristics of the packaged food products, and are safe for consumption. One of the ingredients that can be added to edible film is Aloe vera skin. The study aimed to determine the effect of increasing the aloe vera leaf extract concentration and producing an antibacterial edible film with the appropriate mechanical and antibacterial inhibitory properties. The study used a completely randomized design. Observations of film’s characteristics included mechanical and physical properties i.e., tensile strength, elongation, modulus of elasticity, water vapor transmission rate, thickness, CIE color values, and the inhibition activity of bacterial growth. The obtained data were analyzed using analysis of variance (ANOVA), and if there was a significant difference, Duncan’s Multiple Range Test was applied. The best edible film was obtained by adding aloe vera skin extract at a concentration of 4 times the Minimum Inhibitory Concentration (MIC). This film had a tensile strength of 0.878 MPa, elongation of 75.56%, modulus of elasticity of 1.16 MPa, thickness of 0.153 mm, Water Vapour Transmission Rate (WVTR) of 22.53 g/(m2.day), inhibition activity of 31.85 mm, and color value CIE ∆L* = 18.61, ∆a* = 0.98, ∆b* = 29.57, ∆E* = 38.63, ∆C*= 33.59, and ∆H* = -87.23 with the white plate color of chromameter used as a standard.